PERKEMBANGAN EKSPOR DAN STRATEGI PAKAIAN JADI INDONESIA PERIODE 2012 –2016 - Adelia Happy Rizky R.; Ahmad Zafrullah TN.; Made Siti Sundari (Perpustakaan Universitas Surabaya, 2018)
This paper discusses the development and strategies of export apparel in Indonesia period 2012 –2016. The purpose of this study is to analyze the development of Indonesia’s apparel exports over period of 5 years ( 2012 –2016 ). This research uses descriptive qualitative method to improve the condition that happened about Indonesia’s apparel. The data used in the research is apparel data from 2012 –2016 obtained by government agencies and literature study. The result show that the development of apparel export in 2012–2013 has increased steadily. But in 2013 –2016 the export of apparel has decreased continuously because of the sluggishness of the world economy and the tightness of international market competition and some strategies can be done by the business and the government’s support for the apparel.